Work Discipline and Employee Performance: Empirical Evidence from a Banking Unit - Ilham Slamet Riyadi; Zaenal Abidin; Alisyah Pitri; Erwina Kartika Devi (Journal of Innovative and Creativity, 2025)
The study aimed to examine the effect of work discipline on employee performance at X bank units. Human resources, as the primary element of any organization, play a crucial role in achieving institutional goals. Among the various factors that influence employee performance, work discipline is a key determinant. Poor time discipline and non-compliance with company regulations often result in decreased performance, highlighting the need to investigate the relationship between these variables. Materials and methods. This quantitative research employed both primary and secondary data, using a descriptive analysis method, classical assumption tests, simple linear regression analysis, coefficient of determination, and t-test hypothesis testing. The data were processed using SPSS version 22 to examine the extent to which work discipline influences employee performance. Results. The results showed that work discipline had a positive and significant effect on employee performance at X bank units. The analysis revealed that work discipline contributed 31.4% to performance outcomes, while the remaining 68.6% was influenced by other variables not included in this model. The regression equation obtained was Y = 24.147 + 0.605X, and the t-test results indicated that the calculated t-value (3.884) exceeded the critical value (2.035), confirming a statistically significant effect. Conclusions. The findings underscore the importance of enhancing employee discipline to improve performance in the banking sector. The study contributes to the literature by integrating Islamic work values in the context of work discipline and its practical implications for human resource management in creating a more productive and goal-oriented workplace.